Innovative assessment approaches of creativity - Palaniappan, A.K.; Teh, Y.W.; Subramaniam, S.R. (2008)
Assessment of any cognitive dimension has always been a challenge. More so if the construct that is being assessed has eluded accurate definition since gaining prominence. One such cognitive is creativity. Assessing creativity has always been a challenge since there is no one definition that has been universally accepted. One definition that comes close is Torrance's (1974) definition which has led to the development of the world famous creativity tests - Torrance Tests of Creative Thinking (TTCT). However, TTCT have been known to be a battery of tests that require would-be scorers to undergo training which is only available at the University of Georgia's Torrance Center for Creative Studies. This makes it difficult for users of this test to be trained before they are certified to score these tests accurately and reliably. Hence, many users of the TTCT have resorted to scoring the tests based on their readings from manuals and other sources. This paper will discuss one innovative approach that has been designed to not only assess creativity using an adapted version of TTCT quickly but also easily by any users anywhere in the world through the web-based creativity assessment system or WBCAS. Research findings will be presented to show that this system can be used to assess one's creativity quickly and accurately. This paper will also discuss some of the other advantages of using WBCAS in assessing creativity.